Supervisory technology as a new tool for banking sector supervision - Tomasz Dziawgo (Journal of Banking and Financial Economics (JBFE), 2021)
After last global financial crisis from a decade ago, financial market have been experiencing significant increase in number of regulations. This was especially visible in the banking sector, in which number of post-crisis new regulations amounted to thousands per year. It was not only challenging for banks, that have been spending increasingly more financial resources on compliance, but also for supervisory entities that have to keep track of compliance for every entity on financial market. Due to the fact that supervisory process relies mostly on manual process, it can be both time consuming and inefficient. This is why, not only banks have been exploring new technologies in compliance with regulations (Reg Tech), but also supervisory authorities have been doing the same with the aim of increasing their efficiency (Sup Tech). The research paper aims to test hypothesis, which is as follows: - Sup Tech is becoming an innovative tool for banking supervision and is expected to have increasingly larger role in banking supervision For the purpose of the paper, the following methods have been applied: critical analysis of literature and research papers as well as descriptive method and comparative analysis of presented data.
Keywords: E42; G21; O14; 330; Supervisory Technologh; Supervisory Authority; Sup Tech